The Provisions of Crime Prevention Programs in Lithuania: Between Absurdity and Quality - SAKALAUSKAS, GINTAUTAS (Kriminologijos studijos, 2017)
The idea of crime prevention is very simple. However, the reality of its effectiveness and the real possibilities of changing something significant within the society are much more complicated. The quality of different crime prevention programs depends on the competence and true purposes of their creators. Criminological knowledge is very important for the development and evaluation of crime prevention measures. There are a lot of crime prevention programs in Lithuania, designed for different fields of criminal behavior. Two latest programs were adopted by the Parliament of Lithuania in 2015 and are very different in their quality: The National Anti-Corruption Program 2015-2025 of the Republic of Lithuania and The National Program of Public Security Development 2015-2025 of the Republic of Lithuania. The article deals with the theoretical backgrounds of crime prevention, the criteria of their effectiveness and the ideological context.
Keywords: ...